Penciptaan Manusia Perspektif al-Quran: Kajian Tafsir Tematik Kata al-Insan - Maryam, Shovi; Huda, Miftahul (HERMENEUTIK : Jurnal Ilmu al-Qur'an dan Tafsir, 2022)
The Creation of Man in Quranic Perspective: the Study of Thematic Interpretation of the Words of al-Insan. This study aims to describe the word al-Insan in the Quran in terms of language, interpretation, asbab al-nuzul, and the values of its content. This study is library research with qualitative approach. The data analysis technique adopted the qualitative data analysis technique of Miles and Huberman combined with the thematic study of the Qur'anic interpretation. The results show the word al-Insan in Quran was mentioned 65 times. In terms of language, al-Insan means docile or friendly, forgetful, and knowing. The word al-Insan in Quran discusses human comprehensively which consists of physical and psychological. This is explained from the various uses of the word al-Insan in the Quran about the process of human creation, about human nature, and human tasks and the value of human’s education. Inside the good and bad potential of humans, they carry the mandate to obey God. So that humans do not lose in this world and the hereafter, Allah gives the keys to education, including discipline education, time management, faith, good deeds, and mutual advice in truth and patience.